Peningkatan Hasil Belajar IPA Materi Organ Pencernaan Manusia Melalui Model Pembelajaran Problem Based Learning - Nurul Ariyanti (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The purpose of this study was to determine the increase in science learning outcomes for the material of human digestive organs through the Problem Based Learning learning model in class V Semester I SD Negeri Bintoro 13 in the 2019/2020 academic year. The subjects of this study were the fifth grade students of SD Negeri Bintoro 13 in the 2019/2020 academic year, totaling 15 students. The research design was classroom action research consisting of two cycles, namely cycle I and cycle II. Each cycle consists of 2 meetings. Data collection was obtained from the results of tests and observations. While the data analysis includes qualitative data and quantitative data. In the first cycle, the classical completeness was 60.00%. While in the second cycle of 86.67%. These results indicate that the Problem Based Learning model in science learning material on human digestive organs can improve the learning outcomes of fifth grade students at SD Negeri Bintoro 13 Demak.